Valuasi Harga Wajar Saham dengan Metode Discounted Cash Flow dan Relative Valuation pada Rencana IPO PT Pertamina International Shipping - Putra, Alghifari Arsa (Riviera Publishing, 2025)
This study aims to evaluate the fair value of PT Pertamina International Shipping (PIS) shares in preparation for its planned Initial Public Offering (IPO) in 2025. The research applies the Discounted Cash Flow (DCF) and Relative Valuation methods to obtain a comprehensive estimation of the company’s intrinsic value. Data were collected from PIS’s financial statements for 2019–2024 and from ten comparable companies in the maritime logistics and shipping sector. The results show that the fair value of PIS shares using the DCF method with the Free Cash Flow to the Firm (FCFF) approach is IDR 1,531 per share; the Free Cash Flow to Equity (FCFE) approach yields IDR 1,566 per share; and the Relative Valuation using the Price to Earnings Ratio (PER) method gives IDR 976 per share. After reconciliation with weighted averages of 40% for DCF-FCFF, 40% for DCF-FCFE, and 20% for Relative Valuation, the final fair value estimate is IDR 1,434 per share. These findings indicate that PIS shares possess strong financial fundamentals and improved operational efficiency, offering promising long-term investment potential for investors.